1994
DOI: 10.1002/jhet.5570310623
|View full text |Cite
|
Sign up to set email alerts
|

The utility of the PM3 method for predicting the reactivities of cyanoethenes in diels‐alder reactions with pyrrole

Abstract: The reliability of PM3 for predicting the reactivity of cyanoethenes in Diels‐Alder reactions with pyrrole was tested. Using frontier orbital theory it was predicted that the reaction is LUMO dienophile controlled, and the reaction should be facilitated in comparison to cyclopentadiene additions (pyrrole has higher HOMO energy). The transition structures were generated and compared with similar ones generated with both ab initio and PM3 calculations for cyclopentadiene additions: The geometries of the transiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…The two most up-to date computational studies of the CDA active site by Lewis et al [19,20] provide specific structures of the substrates. However, some alternative protonation states of the reaction model, which seem plausible, were not evaluated by Lewis et al, and the stationary points obtained using the semiempirical approach may not always be conclusive [21,22].…”
Section: Introductionmentioning
confidence: 98%
“…The two most up-to date computational studies of the CDA active site by Lewis et al [19,20] provide specific structures of the substrates. However, some alternative protonation states of the reaction model, which seem plausible, were not evaluated by Lewis et al, and the stationary points obtained using the semiempirical approach may not always be conclusive [21,22].…”
Section: Introductionmentioning
confidence: 98%
“…It has been reported that tetrazoles cover a wider spectrum of bioactive heterocycles with azapyrrole system 16,23,24 . These compounds have been used for both biological and nonbiological applications [25][26][27] . Among several types of tetrazoles, 5-amino -1-substituted derivatives have been reported as antibacterial, antiviral, anti-inflammatory and antiallergic agents [28][29][30] .…”
Section: Introductionmentioning
confidence: 99%
“…We recently studied theoretically the suitability of pyrrole as diene for the Diels-Alder reaction for the cycloaddition reaction (9). The predicted activation energies are too high even for the Diels-Alder reaction in the case of pyrrole acting as diene.…”
Section: Introductionmentioning
confidence: 99%